(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Magnesium Sulphate and Dexamethasone are used as adjuvants to local anaesthetics in regional anaesthesia to improve the quality of block Objective: To compare the efficacy of magnesium sulphate and dexamethasone on the characteristics of the block and its effect on postoperative analgesia when added as an additive to bupivacaine in supraclavicular brachial plexus block. Materials and Methods: Fifty patients belonging to American Society of Anaesthesiologists (ASA) Grade I and II, aged between 18 to 55 years, scheduled for elective upper limb surgeries under supraclavicular brachial plexus block were enrolled in this study. Patients were equally divided into two groups : group M received 0.5% Bupivacaine 30ml with 10% Magnesium sulphate 5 ml (500mg) and group D received 0.5% Bupivacaine 30ml with Dexamethasone 2ml (8mg) + Normal saline 3ml. Onset and duration of sensory and motor block , duration of postoperative analgesia and any complications were observed. Results: In our study the demographic profile of patients, duration of surgery and ASA status between the two groups were comparable. Onset of sensory block was earlier in group D than group M (17.12±0.93 minutes and 19.40 ±1.08 minutes respectively, p=0.001). Duration of motor block and analgesia were longer in group D as compared to group M (479.00 ±50.83 minutes vs 346.40 ±32.77 minutes respectively, p= 0.001 for motor block and 533.80 ±59.80 minutes vs 415.00 ±57.23 minutes respectively, p=0.001 for analgesia). No significant side effects were noted. Conclusion: Dexamethasone is a better adjuvant than Magnesium Sulphate when added to bupivacaine in supraclavicular brachial plexus block as it prolongs duration of motor block and analgesia significantly with minimal side effects.